Motif Penggunaan Second Account Instagram Sebagai Media Interaksi Diri (Studi Kepada Mahasiswa Ilmu Komunikasi Tahun 2019 Universitas Mulawarman) - Maulidya, Sarah; Alfando, Johantan; Nurliah; Purwanti, Silviana (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
The phenomenon of second account Instagram is increasing because it provides individuals with the opportunity to build different social identities and interactions that may not be shown in the main Instagram account. The purpose of this study was to determine the motives for using second Instagram accounts as a medium of self-interaction in 2019 Communication Science students at the University. This research uses qualitative methods with a qualitative descriptive approach and is based on the theory of self-disclosure by Altman and Taylor. Data collection techniques are observation, interview, and documentation. In the interview, six resource persons were obtained using purposive sampling technique. The results showed that Communication Science students in the 2019 batch of Mulawarman University used Instagram second accounts as a medium of self-interaction with motives that developed over time in accordance with the five aspects of Altman and Taylor's (1975) self-disclosure theory.